Simulation of Harmonic Mitigation in the Crusher System: A study at A Coal Company in Borneo - Bintang Bhakti Nugraha; Ridha Yasser; Wahdiyatun Nisa (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
In the coal mining industry environment of PT. Baramulti Suksessarana Tbk (BSSR), the issue of electrical energy quality receives special attention, particularly due to the use of non-linear equipment such as induction motors which trigger harmonics. These harmonics impact operational efficiency and affect equipment. This study aims to address this issue by designing a Single tuned passive harmonic filter, following IEEE standards, to handle the increase in Total Harmonic Distortion (THD) of current and voltage. From the initial analysis, the system's THD was recorded at 20.04%, indicating significant harmonic disturbances. With a specific harmonic filter design, including capacitor values, inductive reactance (XL), and resistors, this study successfully reduced the THD to 5.55%, demonstrating the effectiveness of the filter in reducing the negative impact of harmonics. The conclusion of this study highlights the importance of implementing passive harmonic filters in improving the quality of electric power in industrial environments, especially in the BSSR coal mine. This research provides essential guidance for practitioners in designing harmonic filters and contributes to improving the quality of electric power in the coal mining industry.